2002
DOI: 10.1136/gut.50.5.599
|View full text |Cite
|
Sign up to set email alerts
|

You get what you expect? A critical appraisal of imaging methodology in endosonographic cancer staging

Abstract: Background and aims: After an initial period of excellent results with newly introduced imaging procedures, the accuracy of most imaging methods declines in later publications. This effect may be due to various methodological factors involved in the research. Using the example of endoscopic ultrasound (EUS), this study aimed to elucidate one of the factors possibly concerned-namely, the extent to which the examiners are adequately blinded. Methods: Well documented videotapes of EUS examinations of 101 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 31 publications
4
64
1
3
Order By: Relevance
“…The secondary search (Table 2) identified 2828 publications with the full text retrieved for 34: ultimately 6 were included [6,13,[26][27][28][29] and 28 rejected because the research focused on case-specific information. The tertiary search (Table 3) identified 74 MeSH terms which were combined into 18 Boolean search strings: These identified 111 potential articles with a further 2 via snowballing; 5 articles were ultimately included [11,12,[30][31][32]. Overall, 11247 abstracts were reviewed, 201 full articles retrieved, and 12 ultimately included for systematic review ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The secondary search (Table 2) identified 2828 publications with the full text retrieved for 34: ultimately 6 were included [6,13,[26][27][28][29] and 28 rejected because the research focused on case-specific information. The tertiary search (Table 3) identified 74 MeSH terms which were combined into 18 Boolean search strings: These identified 111 potential articles with a further 2 via snowballing; 5 articles were ultimately included [11,12,[30][31][32]. Overall, 11247 abstracts were reviewed, 201 full articles retrieved, and 12 ultimately included for systematic review ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of conventional EUS in differentiating lower T-cate gories uT1/T2 from advanced categories uT3/T4 in gastric and esophageal cancers were 93% and 91% in very experienced hands, res pectively. Some studies, however, showed a lower accuracy for T-staging in the daily clinical routine and it is obvious that reported ac curacies are clearly lower in more recent stud ies (Meining et al 2002). Unfortunately, the accuracy of EUS is highly dependent on the experience of the examiner and showed only a rather modest performance in some studies (Meining et al 2003;Polkowski et al 2004).…”
Section: Endoscopic Ultrasound (Eus)mentioning
confidence: 96%
“…[18]. Auf die hohe Untersucherabhängig-keit wurde allerdings erst kürzlich hingewiesen [19,20]. Die Genauigkeit des endoskopischen Ultraschalls zur Vorhersage der R0-Resektabilität wurde beim Adenokarzinom des Ösophagus mit 89% als sehr zufrieden stellend angegeben; beim Plattenepithelkarzinom des Ösophagus war sie mit 64% allerdings nur mäßig.…”
Section: Präoperative Diagnostikunclassified